Food security in South Africa : human rights and entitlement perspectves - Fukuda-Parr, Sakiko; Taylor, Viviene (Claremont, South Africa : UCT Press, 2015)
Although the term itself was only developed in the 1970s, food security has played a central role in policies that have shaped the history of South Africa from the 17th century. As with the changing international interpretation of food security over the past four decades, South African food security determinants have been interpreted differently by different ruling authorities and governments over three centuries. The Natives Land Act of 1913 played a significant role in determining the food security context of the country in terms of the character, composition and contribution of the agricultural sector, shaped consumption patterns and determined rural livelihoods. While food security is expressed as a national objective in a plethora of strategies and programmes, no formal evaluation has been carried out of the food security impact of these programmes, and there is a dire lack of coordination and no enforceable policy to ensure food security. Any national food security policy will need a framework of enforceable legislative measures and statutory coordination and reporting. This article explores the current national and household food security and nutrition situation in South Africa, and it offers recommendations for a comprehensive food security policy.
Includes bibliographical references and index.
Keywords: Food security -- Africa, Southern; Food supply, Africa, Southern; Agriculture policy